Citizen revolution in Tunisia and regional contagion: lessons for sub-Saharan Africa (2012)
The citizen revolution in Tunisia played a significant role in the changing pattern of politics in North Africa. This article contends that the paternalistic, autocratic and undemocratic nature of North African leaders was responsible for the poor quality and maldistribution of resources among citizens. The revolution which began in Tunisia with a suicide, spread through the region as experienced in Egypt, Algeria and Libya. Across the region, the revolution was inspired by the same social and economic factors, including high unemployment, poverty, decline in real indicators of development and state repression of the opposition. Using the frustration - aggression theory, the paper posits that relative deprivation is a background factor for citizen revolution. Thus, individuals with high expectations are more likely to become frustrated when experiencing hardship and such feelings can drive individuals to address their grievances. Applied to sub-Saharan Africa, the revolution portends a reoccurrence of such phenomenon. This is because authoritarianism, sit-tight governments, succession crisis, corruption and economic inequalities are common endemic problems in the region. The paper concludes that urgent political and economic reforms within the context of good governance will be an antidote for citizen revolution in the current global order